Ancaman Limbah Pertanian Terhadap Air Tanah: Kajian Komprehensif dan Strategi Mitigasi - Maulidya, Annisa; Ihsan, Taufiq (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
This review aims to assess the diversified risks associated with agricultural pollution of groundwater and to propose effective mitigation measures. In that direction, the article discusses the source and pathways of agricultural contaminants, underlining the controlling role of geology in contaminant transport. In this paper, an attempt will be made to assess critically the adverse effects of such contaminants on human health, the environment, and the economy. This requires interdisciplinary approaches to risk assessment and management that involve geologists, hydrologists, agronomists, environmental scientists, policymakers, and farmers. This review, therefore, summarizes good management practices"”including cover cropping, crop rotation, and precision agriculture to minimize chemical use"”and also discusses some regulatory measures, such as groundwater monitoring programs and land-use regulations, put in place for the protection of groundwater quality. Case studies are drawn from different regions of these mitigation strategies through collaborative and multifaceted approaches. The review thus concludes by underlining the need for further research and innovation in technology coupled with the engagement of stakeholders for future sustainability in agriculture without compromising the groundwater resources.